MARKETING RESEARCH METHODS AND POSSIBILITIES OF THEIR APPLICATION IN THE ACTIVITIES OF TEXTILE ENTERPRISES - Azizillayev Mirzo-Ulug‘bek Oybek o‘g‘li (Scholar Express Journals, 2025)
This article examines marketing research methods and their application to textile enterprises. It explores economists' definitions and approaches to the concept of marketing research. The results of a questionnaire analysis and a SWOT analysis of a sample of textile products manufactured by Bitlis Textile LLC are presented. The potential for applying marketing research methods to textile enterprises is demonstrated, and conclusions are drawn
Keywords: textile industry; textile enterprises